2007
DOI: 10.3748/wjg.13.6562
|View full text |Cite
|
Sign up to set email alerts
|

Serum pepsinogen levels and their infl uencing factors: A population-based study in 6990 Chinese from North China

Abstract: AIM:To explore the essential characteristics of serum pepsinogen (PG) levels in Chinese people, by analyzing the population-based data on the serum levels of PG Ⅰ and Ⅱ and the PGⅠ/Ⅱ ratio, and their influencing factors in Chinese from North China. METHODS:A total of 6990 subjects, who underwent a gastric cancer screening in North China from 1997 to 2002, were collected in this study. Serum pepsinogen levels were measured by enzyme-linked immunosorbent assay (ELISA). H pylori status was determined by histologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 15 publications
3
15
2
Order By: Relevance
“…Overall, we had 69 eradicated and 6 non-eradicated patients based on both PGII levels (baseline and post-therapy). In agreement with other studies [30,31,32], the mean level of PGII after eradication therapy was significantly lower with respect to the baseline level in the Hp -eradicated subjects (p = 0.0001).…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…Overall, we had 69 eradicated and 6 non-eradicated patients based on both PGII levels (baseline and post-therapy). In agreement with other studies [30,31,32], the mean level of PGII after eradication therapy was significantly lower with respect to the baseline level in the Hp -eradicated subjects (p = 0.0001).…”
Section: Resultssupporting
confidence: 81%
“…Overall, the use of the Gastropanel kit in our experience confirms the importance of PGII dosage in monitoring Hp infection, while the results are not encouraging in the case of gastric atrophy, besides a minimum utility of the PGI/PGII ratio, in contrast to previous reports [30,31,32,43]. However, in our series, multiple evolutive lesions, such as intestinal metaplasia and gastric atrophy, were present in many cases, and some of these cases showed indicative gastropanel values.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Miki et al used serum PGA < 50 mg/L and PGA/PGC ratio <3.0 in a comprehensive screen of GC in Japan [36]. Sun et al reported that a PGA/PGC ratio <7 is suitable for identifying populations at high risk of GC in Chinese [37]. Tu et al evaluated temporal changes in PGA and PGC levels and PGA/PGC ratio with the risk for progression of gastric precancerous lesions and suggested that increased serum PGA and PGC and decreased PGA/PGC ratio were associated with risk for progression of gastric precancerous lesions [38].…”
Section: Pgc Expression and Cancermentioning
confidence: 99%
“…The detailed method of examination of serum pepsinogens has been described in our previous study [14]. Approximately 5 ml fasting blood was collected from each participant.…”
Section: Methodsmentioning
confidence: 99%